Accessing Planktothrix species diversity and associated toxins using quantitative real-time PCR in natural waters - Churro, Catarina (2012)
Fundação Ciência Tecnologia através do projecto:PTDC/AMB/67075/2006 e Bolsa de Doutoramento da FCT SFRH/BD65706/2009.